Suture constructs for rehabilitation using early active motion after tendon transfer surgery. (November 2018) - Fitzgerald, Michael G.; Hammond, Max A.; Yang, Patrick W.; Merrell, Gregory A.
The purpose of this study was to better define an ideal tendon transfer suture construct to allow for early active range of motion. A side-to-side tendon construct was used to test suture technique (cross stich vs. Krackow stitch), number of suture throws, and calibre of suture. A minimum load to failure of 100 N was used to comfortably allow early motion while minimizing rupture risk. All constructs tested, except the 4-0 Krackow construct, were strong enough to withstand 100 N of load. The choice of suture should be based on surgeon preference, patient compliance, and specific surgery, and 3-0 non-absorbable suture may be more suitable for tendon transfers from a yield force standpoint.